Une révolution presque sereine : la déségrégation des écoles à Washington en 1954 - Ludivine Gilli (Transatlantica)
The Supreme Court decision Brown v. Board of Education of Topeka of 17 May 1954, which declares segregation in public schools unconstitutional, was poorly received in the Southern states. In the federal capital, however, several factors contributed to a swift and smooth transition from this historically entrenched dual system towards desegregation. Led by a determined president, the federal government set the tone by requiring immediate action from local authorities. The dual school system was decidedly unequal, and segregation had become a clear obstacle to the resolution of its structural dysfunctions. Beginning in 1947, parents and civic organizations protested relentlessly in the streets and in the courts, after local activists had obtained the end of segregated theaters as early as 1946. No major unrest ensued, which alleviated concerns and contributed to making full desegregation appear inevitable. In this favorable context, civic organizations and authorities worked early to prepare for the implementation of desegregation in Washington D.C.’s school, which resulted in a peaceful transition.